2022
DOI: 10.1186/s12979-022-00278-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal profiling of clonal hematopoiesis provides insight into clonal dynamics

Abstract: Background Clonal hematopoiesis of indeterminate potential (CHIP), the age-related expansion of mutant hematopoietic stem cells, confers risk for multiple diseases of aging including hematologic cancer and cardiovascular disease. Whole-exome or genome sequencing can detect CHIP, but due to those assays’ high cost, most population studies have been cross-sectional, sequencing only a single timepoint per individual. Results We developed and validated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
2
20
1
Order By: Relevance
“…35 Generally, this is indicative of greater mutational fitness as recently characterized through recent longitudinal studies of CHIP. [118][119][120][121][122] Given the commonality at advanced age, increasingly limited clonal diversity was posited to be a characteristic feature of normal aging. 120 Despite mutations in DNMT3A being more common among individuals with CHIP, DNMT3A clones generally grow slower compared to other driver mutations.…”
Section: Insights From Longitudinal Analysesmentioning
confidence: 99%
“…35 Generally, this is indicative of greater mutational fitness as recently characterized through recent longitudinal studies of CHIP. [118][119][120][121][122] Given the commonality at advanced age, increasingly limited clonal diversity was posited to be a characteristic feature of normal aging. 120 Despite mutations in DNMT3A being more common among individuals with CHIP, DNMT3A clones generally grow slower compared to other driver mutations.…”
Section: Insights From Longitudinal Analysesmentioning
confidence: 99%
“…Clonal hematopoiesis of indeterminate potential (CHIP) is defined by the presence of somatic pathogenic variants in leukemia associated driver oncogenes, present at a variant allele frequency (VAF) of ≥2% (2% threshold was arbitrarily chosen due to the lower limit of detection of most next‐generation sequencing assays), in the absence of cytopenias, cytosis or bone marrow (BM) dysplasia. CH with somatic variants at VAF below 2% are also detectable with higher sensitivity assays such as error corrected and deep targeted sequencing, but longitudinal studies have shown that most of these variants largely remain static or shrink over time, suggesting that majority might not be clinically relevant 16 . When individuals with CH have persistent (≥4 months) cytopenias [defined as the presence of acquired and sustained anemia (hemoglobin <12 g/dL in females and <13 g/dL in males), neutropenia (absolute neutrophil count <1.8 × 10 9 /L), and/or thrombocytopenia (platelets <150 × 10 9 /L), that is not explained by an alternate etiology], a diagnosis of clonal cytopenia of undetermined significance (CCUS) can be made 17 .…”
Section: Ch Terminologymentioning
confidence: 99%
“…CH mutations are generally detected later in life (age >50 years) but with sensitive assays (error‐corrected sequencing), smaller clones have been detected in younger individuals 30 . Clones less than 2% VAF however, have a less propensity to expand over time, however this is heavily dependent on variant‐specific fitness impact and environment 16 . Specific driver mutations, in particular JAK2 V617F has been predicted to occur in‐utero from phylogenetic reconstruction of clones in myeloproliferative neoplasms 31 .…”
Section: Clonal Fitness and Selection Pressuresmentioning
confidence: 99%
See 2 more Smart Citations